Retrospective - Pillay, Previn (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of poems, divided into 4 sections. The first section draws on my experiences and background as an Indian South African, presenting a portrait of a KwaZulu-Natal Indian community, infused with the lingo of the streets. It also delves into my background by sharing real stories from my childhood and youth. The second section is about my grandmother, who is an influential character on my writing and a source for many unique stories. The third section is a brief look at my recent past and the fourth section is a sharing of my life and what is most important to me. My collection is a timeline of my life and the events which have shaped me.
Keywords: Creative writing (Higher education) -- South Africa; South African poetry (English) 21st century; Identity (Philosophical concept) in literature; Grandmothers in literature; Families in literature